Estimation of safe yield in Mannar Island, Sri Lanka - Amaraweera, H. B. M. P.; Gupta, Ashim Das; Suphat Vongvisessomjai; Loof, Rainer; The Canadian International Development Agency-A.I.T. Partnership Program (Bangkok : Asian Institute of Technology, 1990)
Commercial developments in the island of Mannar in Sri Lanka over the past few years have made estimation of safe yield a very important requirement. But this estimation process is complicated due to the absence of sufficient field data and the occurrence of aquifer as a thin lens floating over saline water. This study is an attempt towards applying approximate solution to analyse this problem. The first approximation of the recharge to the fresh water lens is obtained by a Water Balance Study incorporating Hydrological Budget and Soil Moisture Balance. During the estimation, 36 trials are generated considering the factors influencing soil moisture balance. The recharge estimation done in this part of the study are refined by the analysis of fresh-salt water interface movement. For this purpose, approximate solutions derived by HANTUSH (1968) are used with relevant modification to the study area. An abstraction rate of 1.5 times the present level (1988) is found to be safe on the long term basis. It is also found from this study, that during a drought period, doubling of the present level of abstraction is not undesirable for a limited period of time, but careful monitoring of chloride content of pumped water has to be accompanied.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Water, Underground -- Sri Lanka